The Utilization of Cosmetic Plants: An Ethnobotanical Study in Indonesia - Peniwidiyanti, Peniwidiyanti; Hasanah, Ida Farida; Rahayu, Mulyati (Al-Kauniyah: Jurnal Biologi, 2026)
Indonesia has a long history and development of plant utilization for cosmetics; until now, various cosmetic products have been mass-produced and can slowly eliminate the traditional knowledge of local communities on plants that have potential as cosmetics. This study aims to provide information about the types of potential cosmetic plants used by people from several regions in Indonesia. The methods used were open-ended, non-structured interviews and direct observation in the field. The research was conducted in five locations from four provinces (Banten, West Java, West Nusa Tenggara, and Southeast Sulawesi), and 34 plant species from 24 families were recorded. The Zingiberaceae family is the group with the highest number of species, at four. Fruit was the most utilized plant part at 35.2%, followed by flowers and leaves. Most recorded plants were used in skin care (40.38%). Santalum album is one of the plant species that is utilized and is now included as one of the threatened plant species, and there is a need for conservation efforts for this species.